Validity and Practicality of Discovery Learning E-Modules on environmental change material to Empower Critical Thinking Skills - Wulan Aprilia Utami; Harlita Harlita; Puguh Karyanto (Jurnal Penelitian Pendidikan IPA, 2022)
Critical thinking ability is a way of thinking to determine the right decision or action by logically considering things related to information. Therefore, it is necessary to update what supports learning activities, such as updating the suitable media by utilizing technological sophistication. This study aims to determine the validity and practicality of the discover learning e-module on environmental changes to empower critical thinking skills. This research type uses the ADDIE model development (Analysis, Design, Development Implementation, Evaluation). This study is limited to testing the validity and practicality of the e-module. The instrument used is a validity and practicality questionnaire. Assessment of the results of the validity and practicality of the questionnaire was interpreted with a Likert scale. Based on data analysis, the results of the validity test by material experts, and media experts, obtained an average score of 89% and 92%, respectively, in the very good category. And on the test of education, practitioners by teachers and students obtained an average value of 91% and 88%, which fall into the very good category. Based on the validity test and practicality test, it can be concluded that the e-module developed is valid and practical for use in further research